2021
DOI: 10.1186/s12937-021-00686-5
|View full text |Cite
|
Sign up to set email alerts
|

The effect of grape products containing polyphenols on oxidative stress: a systematic review and meta-analysis of randomized clinical trials

Abstract: Background The literature showed that Grape Products Containing Polyphenols (GPCP) had anti-oxidant activity. However, the effects of GPCP on different biomarkers of oxidative stress are still controversial. In this regard, this systematic review and meta-analysis aimed to evaluate the effect of Grape Products Containing Polyphenols (GPCP) intake on oxidative stress markers. Methods PubMed, Scopus, Web of Science, and Google Scholar data bases were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 134 publications
0
9
0
Order By: Relevance
“…In a meta-analysis of 17 RCTs involving grape polyphenol supplementation, significant increases in antioxidant capacity and SOD activity were observed in healthy volunteers. Interestingly, no differences were noted in other antioxidant enzyme markers [ 32 ]. In another study of healthy humans, a 4-week supplementation of acai berry juice significantly increased total blood antioxidant capacity, as well as catalase and GPX activities [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…In a meta-analysis of 17 RCTs involving grape polyphenol supplementation, significant increases in antioxidant capacity and SOD activity were observed in healthy volunteers. Interestingly, no differences were noted in other antioxidant enzyme markers [ 32 ]. In another study of healthy humans, a 4-week supplementation of acai berry juice significantly increased total blood antioxidant capacity, as well as catalase and GPX activities [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…A double-blind randomized clinical trial revealed that grape consumption increases the total antioxidant capacity in the body which will help to fight oxidative stress and inflammation (Sarkhosh-Khorasani et al, 2021). In another study, it is found that grape extract significantly attenuates the body weight and mass index, waist circumference, as well as waist-to-hip ratio and also lower TNF-α, and high sensitivity C-reactive protein levels (Parandoosh et al, 2020) .…”
Section: Clinical Studies Of Grapementioning
confidence: 99%
“…A recent meta-analysis of random clinical trials demonstrated the effective role of PPs on oxidative stress and inflammation. The findings of this meta-analysis described the potential role of PPs in increasing tacrolimus (TAC) levels [ 54 ]…”
Section: Polyphenols In the Prevention And Treatment Of Different Met...mentioning
confidence: 99%